Preclinical Characterization of GLS-010 (Zimberelimab), a Novel Fully Human Anti-PD-1 Therapeutic Monoclonal Antibody for Cancer - Lou, Beilei; Wei, Hua; Yang, Fang; Wang, Shicong; Yang, Baotian; Zheng, Yong; Zhu, Jiman; Yan, Shaoyu (Frontiers in Oncology, 2021)
Background: Zimberelimab (GLS-010) is a novel fully human immunoglobulin G4 (IgG4) monoclonal antibody against the programmed cell death-1 (PD-1) receptor. Aim: To evaluate the affinity, competitive blocking capability, T cell activation effect, cytotoxic effector functions by Fc, preliminary anti-tumor activity, and pharmacokinetics of GLS-010. Methods: The affinity of GLS-010 to PD-1 and the capability of GLS-010 to block PD-L1 interaction with PD-1 on the cell surface were measured, and the capability of GLS-010 to interrupt PD-L1/PD-L2 interaction was tested. The allogeneic mixed lymphocyte reaction was conducted to evaluate the inhibitory effect of GLS-010 on Tregs and stimulatory effect on T cell proliferation and activation. Pharmacodynamics and pharmacokinetics were evaluated in tumor-bearing mice and cynomolgus monkeys, respectively. Results: The equilibrium dissociation constant (KD) for the association between GLS-010 and PD-1 was 1.75×10-10 M. GLS-010 could effectively block the binding of PD-L1/2 to PD-1. GLS-010 showed statistically significant anti-tumor effects in the MC38 model in human PD-1 knock-in mice. The RO rate on in the low-, middle-, and high-dose groups were 64.50%-48.53% in CD3+T, 58.87%-40.12% in CD8+T, and 66.26%-49.07% in CD4+T, respectively. With the increasing dose from 2 mg/kg to 18 mg/kg, the systemic exposure level of GLS-010 (AUC0-last) and C0 increased proportionally, while the proportion of AUC0-last was slightly higher than the C0. Conclusions: As a fully human anti-PD-1 monoclonal antibody, GLS-010 has a high affinity to PD-1 and in vivo and in vitro anti-tumor effects. The results support that GLS-010 could be investigated in clinical trials in tumor patients.